Method to Calculate the Electricity Generated by a Photovoltaic Cell, Based on Its Mathematical Model Simulations in MATLAB - Carlos Morcillo-Herrera; Fernando Hernández-Sánchez; Manuel Flota-Bañuelos (International Journal of Photoenergy)
This paper presents a practical method for calculating the electrical energy generated by a PV panel (kWhr) through MATLAB simulations based on the mathematical model of the cell, which obtains the “Mean Maximum Power Point” (MMPP) in the characteristic V-P curve, in response to evaluating historical climate data at specific location. This five-step method calculates through MMPP per day, per month, or per year, the power yield by unit area, then electrical energy generated by PV panel, and its real conversion efficiency. To validate the method, it was applied to Sewage Treatment Plant for a Group of Drinking Water and Sewerage of Yucatan (JAPAY), México, testing 250 Wp photovoltaic panels of five different manufacturers. As a result, the performance, the real conversion efficiency, and the electricity generated by five different PV panels in evaluation were obtained and show the best technical-economic option to develop the PV generation project.